Discovery and Validation of a Three-Cytokine Plasma Signature as a Biomarker for Diagnosis of Pediatric Tuberculosis - Kumar, Nathella Pavan; Hissar, Syed; Thiruvengadam, Kannan; Banurekha, Velayuthum V.; Suresh, N.; Shankar, Janani; S, Elilarasi; N S, Gomathi; S, Kalpana; J, Ganesh; M A, Aravind; Baskaran, Dhanaraj; et al. (Frontiers in Immunology, 2021)
Pediatric TB poses challenge in diagnosis due to the paucibacillary nature of the disease. We conducted a prospective diagnostic study to identify immune biomarkers of pediatric TB and controls (discovery cohort) and obtained a separate “validation” cohort of confirmed cases of pediatric TB and controls. Multiplex ELISA was performed to examine the plasma levels of cytokines. Discovery and validation cohorts revealed that baseline plasma levels of IFN, TNF, IL-2 and IL-17A were significantly higher in active TB (confirmed TB and unconfirmed TB) in comparison to unlikely TB children. Receiver operating characteristics (ROC) curve analysis revealed that IFN, IL-2, TNF andIL-17A (in the discovery cohort) and TNFandIL-17A (in the validation cohort) could act as biomarkers distinguishing confirmed or unconfirmed TB from unlikely TB with the sensitivity and specificity of more than 90%. In the discovery cohort, cytokines levels were significantly diminished following anti-tuberculosis treatment. In both the cohorts, combiROC models offered 100% sensitivity and 98-100% specificity for a three-cytokine signature of TNFIL-2 and IL-17A, which can distinguish confirmed or unconfirmed TB children from unlikely TB. Thus, a baseline cytokine signature of TNF, IL-2 and IL-17A could serve as an accurate biomarker for the diagnosis of pediatric tuberculosis.